Composition for direct production of ceramic matrix composites
By using a composition of thermoplastic elastomer and low-density polyethylene, combining inorganic particles and discontinuous fibers, the ceramic matrix composite material is directly produced, and the shape and density problems of the production of ceramic matrix composite materials in the prior art are solved, and complex shapes are achieved Efficient preparation and high density of components.
Patent Information
- Application Number
- CN202280086875.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-28
- Filing Date
- 2022-12-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing direct production methods are difficult to effectively utilize the raw materials of ceramic matrix composite materials, which limits the preparation of complex-shaped components.
The ceramic matrix composite components are directly produced by melting techniques or fuse manufacturing methods using a composition containing thermoplastic elastomer and low density polyethylene, filled with inorganic particles and discontinuous fiber reinforced materials.
Direct production of ceramic matrix composites without adjustment of the print head, especially components with complex shapes, improves interlayer connection and densification levels and reduces crack formation in the degreasing step.
Smart Images

Figure BDA0004918120440000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of direct production and, more particularly, to raw materials suitable for the direct production of ceramic matrix composite parts. Background Art
[0002] Direct production is a technological approach that is gaining increasing attention, especially for the production of components with complex geometries.
[0003] Traditionally, direct production methods of parts made of composite materials involve the use of a print head (eg guided by a computer) to deposit or print the raw material according to a three-dimensional geometry corresponding to the part to be produced.
[0004] Solidification of the raw material is carried out after each layer is deposited in order to obtain a three-dimensional object after the printing step. This step corresponds to the production of the so-called "green body".
[0005] In order to obtain the final part, a step of removing organic materials must be carried out on the green body, called a debinding step, so as to obtain the so-called "brown body". This step is generally followed by a sintering step to obtain a dense final part. Between the debinding and sintering steps or after the sintering step, other shaping or finishing steps may optionally be carried out.
[0006] Currently, the production of ceramic matrix composites by direct production is limited by the raw materials available for their production and by technological limitations related to the suitability of these raw materials for existing direct production methods.
[0007] The object of the present invention is precisely to provide a raw material which can be used by known direct production methods and enables ceramic matrix composite materials to be obtained. Summary of the invention
[0008] To this end, the inventors propose a composition for directly producing a ceramic matrix composite material, which comprises:
[0009] - a polymer phase comprising at least one thermoplastic elastomer and a low-density polyethylene, the volume content of the polymer phase being between 20% and 80% relative to the total volume of the composition;
[0010] - a filler dispersed in the polymer phase, the volume content of the filler being between 20% and 80% relative to the total volume of the composition, and comprising:
[0011] - a first filler comprising inorganic particles; and
[0012] - A second filler comprising discontinuous fiber reinforcements and / or particles having a size greater than that of the first filler, the volume content of the second filler being from 0% to 50% relative to the total volume of fillers in the composition.
[0013] These compositions can be used with direct production methods, in particular by melt technology (such as extrusion) or fused filament fabrication (FFF) or any other method suitable for thermoplastic raw materials.
[0014] Therefore, the composition enables ceramic matrix composite parts, in particular parts with discontinuous reinforcement, with complex shapes (e.g., hollow shapes or shapes requiring support) to be obtained by existing printing methods without the need to readjust the print heads of these methods. In other words, the composition can be directly used as a raw material for the direct production of composite materials (in particular ceramic matrix composite materials).
[0015] In one embodiment, the volume content of the second filler may be 0%.
[0016] In this embodiment, the composition of the invention enables the formation of a ceramic material by the direct production method described above.
[0017] In one embodiment, the volume content of the second filler may be strictly positive, for example between 0.1% and 50%, preferably between 5% and 50%, or even between 5% and 25%, relative to the total volume of the filler in the composition.
[0018] In this embodiment, the composition of the invention enables the direct production of ceramic matrix composite materials with discontinuous reinforcement in a simpler manner.
[0019] More specifically, the composition described above can be directly applied to already existing direct production processes without the need to modify these processes, in particular the step of forming the green body.
[0020] In one embodiment, the thermoplastic elastomers of the polymer phase can be selected from thermoplastic polyurethane elastomers (TPU), thermoplastic styrene elastomers, thermoplastic copolyester elastomers, thermoplastic copolyamide elastomers (TPA), thermoplastic olefin elastomers according to the classification of standard ISO 18064: 2014. They are preferably selected from thermoplastic styrene elastomers, thermoplastic copolyester elastomers and thermoplastic olefin elastomers.
[0021] In one embodiment, the polyethylene of the polymer phase is selected from low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). According to the test standard ISO 1183-2:2019, their density is generally between 0.91 and 0.94 g / cm 3 within the range.
[0022] In one embodiment, the volume content of the polymer phase is between 40% and 80% relative to the total volume of the composition.
[0023] In one embodiment, the volume content of the polymer phase is between 40% and 65% relative to the total volume of the composition.
[0024] In one embodiment, the volume content of the polymer phase is between 45% and 60% relative to the total volume of the composition.
[0025] In direct production, the polymer phase is no longer present in the final component and is usually removed in a debinding step, while the pores created by the removal of the polymer phase are filled by sintering of the filler material.
[0026] It was observed that the volume content of the polymer phase within the above range produces an optimal porosity level, ie it is not too low, thus ensuring that sintering of the filler fills all the pores, nor too high, otherwise the density of the final part would be too low.
[0027] In one embodiment, a composition for direct production of a ceramic matrix composite comprises:
[0028] - a polymer phase comprising at least one thermoplastic elastomer and a low-density polyethylene, the volume content of the polymer phase being between 40% and 65% relative to the total volume of the composition;
[0029] - a filler dispersed in the polymer phase, the volume content of the filler being between 20% and 80% relative to the total volume of the composition, and comprising:
[0030] a first filler comprising particles selected from silicon carbide (SiC), boron carbide (B4C), silicon nitride (Si3N4), zirconium oxide (ZrO2) and aluminum oxide (Al2O3), or particles of a mixture of these compounds; and
[0031] - a second filler comprising discontinuous fiber reinforcements and / or particles having a size greater than that of the first filler, the volume content of the second filler being 0% to 50% relative to the total volume of the filler in the composition,
[0032] The volume content of the first filler is 25% to 40% relative to the total volume of the composition.
[0033] The volume content of the second filler is 5% to 20% relative to the total volume of the composition.
[0034] In one embodiment, the polymer phase may also comprise polyethylene glycol and / or polyethylene terephthalate.
[0035] In one embodiment, the polymer phase of the composition may comprise:
[0036] - 50 to 98.75% by mass of thermoplastic elastomer, relative to the total mass of the polymer phase;
[0037] - 1.25 to 25% by mass of low-density polyethylene, relative to the total mass of the polymer phase;
[0038] - 0 to 25% by mass, relative to the total mass of the polymer phase, of polyethylene glycol having a molar mass of 5000 to 20,000 g / mol;
[0039] - 0 to 15% by mass of polyethylene terephthalate, relative to the total mass of the polymer phase.
[0040] It has been observed that this polymer phase is suitable for the proposed direct production method and in particular enables good winding of the composition when it is in the form of filaments. In addition, the composition has a uniform viscosity, ensuring good compatibility with conventional print heads. In addition, the composition enables more significant interlayer connections than the prior art methods. It also has good degreasing properties, reducing the formation of cracks caused in the prior art by the removal of organic compounds from the composition.
[0041] In one embodiment, the volume content of the filler is 20% to 60%, preferably 35% to 60%, or even 40% to 55%, relative to the total volume of the composition.
[0042] In particular, in the embodiment where the filler comprises only the first filler, the volume content of the filler is 45% to 55% relative to the total volume of the composition.
[0043] In one embodiment, the composition does not contain any elements other than the polymer phase and the filler dispersed therein.
[0044] In one embodiment, the first filler is particles having a unimodal distribution, the particles having a median size d50 of 1 μm to 15 μm.
[0045] The term "unimodal distribution" shall mean that the sizes of the first filler particle group are distributed about a single average size.
[0046] For example, the particle size distribution around a mean size may be a Gaussian distribution.
[0047] Based on the definition of the median size d50, one would expect the distribution to have as many particles with sizes smaller than the mean as with sizes larger than the mean.
[0048] It is observed that the distribution as described above enables simplified sintering, in particular because the size of the filler is small. With these sizes of the first filler, it is possible to obtain very high densification levels, in particular greater than 95%, in the final part obtained after sintering.
[0049] In another embodiment, the particle size distribution of the first filler may be multimodal.
[0050] The choice of a multimodal particle size distribution makes it possible to modify the rheology of the composition and to increase the filler volume content of the first filler. The increase in the volume content of the first filler in the composition makes it possible to obtain a final densified simplified part.
[0051] In one embodiment, the first filler is selected from particles of silicon carbide (SiC), boron carbide (B4C), silicon nitride (Si3N4), zirconium oxide (ZrO2) and aluminum oxide (Al2O3), or particles of a mixture of these compounds.
[0052] In the embodiment where the filler comprises a first filler and a second filler, the volume content of the first filler is 25% to 50%, for example 25% to 40%, relative to the total volume of the composition.
[0053] The first filler particles may form a ceramic matrix in the final part.
[0054] In one embodiment, the volume content of the second filler is 5% to 35%, such as 5% to 25%, or even 5% to 20%, relative to the total volume of the composition.
[0055] In one embodiment, the content of the second filler is preferably 11% to 42% relative to the filler volume of the composition.
[0056] In one embodiment, the second filler is a discontinuous fibrous reinforcement material, such as discontinuous fibers and / or particles of larger size than the first filler.
[0057] The distinction between particles and fibers can be made by determining the shape factor of the secondary filler.
[0058] Here, the shape factor of an object is understood as the ratio between the longest dimension and the shortest dimension. Thus, a perfectly spherical particle has a shape factor of 1. If the shape factor of an object is between 1 and 3, the object is said to be granular, while when the shape factor of an object is greater than 3, the object is considered to be fibrous.
[0059] For example, the second filler may be short fibers having a shape factor between 3 and 625, preferably between 10 and 65.
[0060] In one embodiment, the second filler is selected from carbon fibers, silicon carbide fibers, oxide fibers, glass fibers and / or silicon carbide particles.
[0061] In another embodiment, the second filler is SiC particles having an average size value d50 between 50 μm and 500 μm, such as between 150 μm and 250 μm.
[0062] In one embodiment, the second filler is a short fiber, the average length of which may be between 50 μm and 5000 μm, preferably between 150 μm and 500 μm, or even between 150 μm and 250 μm.
[0063] In one embodiment, the diameter of the short fibers may be 8 μm to 14 μm.
[0064] The inventors have observed that the above dimensions of the fibers allow, on the one hand, the fibers to be long enough to improve the mechanical properties of the final part, and on the other hand, to be short enough to be easily used in a direct production process. In particular, it has been observed that the above dimensions are compatible with existing direct production process print heads, in particular fuse deposition process print heads.
[0065] In one embodiment, apart from the first filler and, where appropriate, the second filler, no further fillers are present in the composition.
[0066] In one embodiment, the second filler may be coated with an interfacial phase and / or a protective deposit.
[0067] Such deposits can reduce the brittleness of the composite material. Protection of the second filler by the interface phase can reduce the vulnerability of these fillers to oxidation or thermochemical attack that may be encountered in subsequent processing. In addition, the interface phase and / or protective deposits can make the matrix better wetted during the sintering step. In one embodiment, the surface of the second filler can be functionalized, for example, to improve the wettability of the organic compound and / or to improve the chemical compatibility between the filler and the organic compound.
[0068] In another aspect, the present invention also relates to a method for directly producing a ceramic matrix composite component with discontinuous reinforcement, comprising the following steps:
[0069] - depositing a composition as described above;
[0070] - a step of removing the organic phase;
[0071] - a step of densifying the obtained part.
[0072] In one embodiment, the step of removing the organic phase may be performed by heating, for example, to a temperature greater than 1000°C or less than 600°C.
[0073] In one embodiment, this step can be performed under vacuum or under a special atmosphere, in particular under an inert atmosphere, such as under argon.
[0074] In one embodiment, the densification step may be selected from stress-free sintering, stress sintering, spark plasma sintering (SPS) or densification by capillary rise of molten metal.
[0075] In a preferred embodiment, the densification step may be a sintering step performed under stress.
[0076] The inventors have observed that this embodiment makes it possible to obtain, from a composition as described above, a final part having a particularly high density, in particular greater than 95%. DETAILED DESCRIPTION
[0077] The present invention will now be described by means of specific exemplary embodiments, which should not be construed as limiting the invention.
[0078] As mentioned above, the composition according to the present invention comprises a filler dispersed in a polymer phase.
[0079] In one embodiment, the composition of the present invention can be prepared by incorporating a first filler into a polymer phase in a first step and then adding a second filler to the combination in a second step.
[0080] In the case where the second filler is a discontinuous fiber reinforcement, it is possible on the one hand to produce these fillers and introduce them in this form directly into the mixture of polymer phase and first filler.
[0081] This embodiment is particularly preferred when the second filler is coated with a protective coating and / or a mesophase.
[0082] In an alternative embodiment, the composition may be obtained from a mixture of a first filler and long fibers dispersed in a polymer phase, and the long fibers are then ground by mechanical shearing action to directly form the second filler in the composition.
[0083] For example, this embodiment can be carried out in a co-rotating twin-screw mixer.
[0084] In this embodiment, the discontinuous fibers may be added to the polymer phase comprising the first filler at a specific location in the mixer by side feeding.
[0085] The embodiment of obtaining the composition in a mixer makes it possible to ensure a homogeneous distribution of the first filler and the second filler in the composition, which ensures that a ceramic material part having homogeneous properties is finally obtained.
[0086] In one embodiment, the composition is mixed several times before it is used in a direct production process. In other words, the composition according to the invention may be introduced into a mixer, such as a twin-screw mixer, before it is used in a direct production process.
[0087] In one embodiment, the composition can be formed into a raw material that can be used in a direct production process.
[0088] For example, in the case where the fused filament deposition process is selected, the composition may be formed by extrusion spinning using a single screw extruder.
[0089] The fuse deposition method is particularly preferred.
[0090] In embodiments where the direct production process is an extrusion process, the composition can be made into pellets having a size of about 1 to 5 mm and having a cylindrical or spherical shape.
[0091] In embodiments where the direct production process is a fused filament deposition process, the composition may be in the form of continuous filaments, for example having a calibrated diameter, for example less than 3 mm.
[0092] The debinding step of the green body is carried out by heating, introducing a solvent or a combination of these two methods. The purpose of this step is to remove organic materials and thus ensure good densification of the part.
[0093] As mentioned above, this step can be carried out under air or under a specific atmosphere.
[0094] The choice is made based on the nature of the filler. For example, when the filler is a ceramic oxide, processing under air may be appropriate. When the filler is a carbide, it is best to use an inert atmosphere such as argon.
[0095] The degreasing step may be performed at a pressure less than or equal to atmospheric pressure.
[0096] In another embodiment, the defatting step may be performed under supercritical conditions, such as using supercritical CO2.
[0097] After the degreasing step, the brown body is subjected to a densification step to obtain the final part. This densification step enables the fillers to occupy the pores left by the removal of the organic material, thus increasing the density of the final part.
[0098] The choice of process for densification depends on the properties of the first filler and the second filler. More specifically, the sinterability of the debinded part depends not only on the properties of the first filler or the second filler, but also on the interaction between them.
[0099] In particular, it has been observed that when the second filler is a fiber reinforcement, sintering of the component is not simply achieved by simply increasing the temperature. It may be necessary to carry out sintering under stress, in other words by exerting pressure on the component.
[0100] It has been shown that the composition according to the invention makes it possible to obtain ceramic matrix composite parts with discontinuous reinforcement by direct production processes suitable for thermoplastic raw materials. In this way, ceramic matrix composite parts with discontinuous reinforcement are obtained in a simplified manner and / or make it possible to obtain more complex component geometries than are obtainable by other currently known direct production processes for obtaining parts composed of these materials.
[0101] In the present application, the expression "(in) ... to ... (between)" should be understood to include the endpoints.
[0102] Example
[0103] Compositions according to the invention have been prepared and their suitability for additive manufacturing techniques have been tested.
[0104] The composition of Table 1 shows a composition suitable for preparing a filament for a fused deposition process. The composition of Table 1 gives the volume content of the filler component dispersed in the polymer phase relative to the total volume of the composition. Therefore, for each composition, the volume content of the polymer phase is the volume content given by the first filler and the second filler under appropriate circumstances if the required balance is to be supplemented to 100. In each embodiment, the polymer phase includes a thermoplastic elastomer, such as a polyester elastomer and a low-density polyethylene. The symbol "--" in Table 1 means that the second filler is not present.
[0105] [Table 1]
[0106]
Claims
1. A composition for directly producing a ceramic matrix composite material, comprising: - a polymer phase comprising at least one thermoplastic elastomer and a low-density polyethylene, the volume content of the polymer phase being between 40% and 65% relative to the total volume of the composition; - a filler dispersed in the polymer phase, the volume content of the filler being between 35% and 60% relative to the total volume of the composition, and comprising: a first filler comprising particles selected from silicon carbide (SiC), boron carbide (B4C), silicon nitride (Si3N4), zirconium oxide (ZrO2) and aluminum oxide (Al2O3), or particles of a mixture of these compounds; and - a second filler comprising discontinuous fiber reinforcements and / or particles having a size greater than that of the first filler, the volume content of the second filler being 0% to 50% relative to the total volume of the filler in the composition, The volume content of the first filler is 25% to 40% relative to the total volume of the composition. The volume content of the second filler is 5% to 20% relative to the total volume of the composition.
2. The composition according to claim 1, wherein The polymer phase comprises: - 50 to 98.75% by mass of thermoplastic elastomer, relative to the total mass of the polymer phase; - 1.25 to 25% by mass of low-density polyethylene, relative to the total mass of the polymer phase; - 0 to 25% by mass, relative to the total mass of the polymer phase, of polyethylene glycol having a molar mass of 5000 to 20,000 g / mol; - 0 to 15% by mass of polyethylene terephthalate, relative to the total mass of the polymer phase.
3. The composition according to any one of claims 1 or 2, wherein The first filler is particles having a unimodal distribution, the particles having a median size d50 of 1 μm to 15 μm.
4. The composition according to any one of claims 1 to 3, wherein The second filler is selected from carbon fibers, silicon carbide fibers, oxide fibers, glass fibers and / or silicon carbide particles.
5. The composition according to any one of claims 1 to 4, wherein The second filler is a fiber having a length of 150 μm to 250 μm.
6. A method for the direct production of a component made of a ceramic matrix composite material with discontinuous reinforcement, comprising the following steps: - depositing the composition according to any one of claims 1 to 5; - a step of removing the organic phase; - a step of densifying the obtained part.
7. The direct production method according to claim 6, wherein: The densification step is a sintering step performed under stress.
Citation Information
Patent Citations
3D printing method of directional short-fiber reinforced metal or ceramic-based composite material
CN110229011A
Material systems for additive manufacturing
CN110312582A
Composition for 3D printing complex ceramic and / or metallic shaped bodies having a higher mecanical strength after debinding and before sintering
WO2021219705A1